PENGARUH MOTIVASI BELANJA HEDONIS, GAYA HIDUP BERBELANJA, DAN PROMOSI PENJUALAN TERHADAP PEMBELIAN IMPULSIF DI OUTLET H&M HARTONO MALL YOGYAKARTA - Nurul Hidayati; Audita Nuvriasari (MANAJEMEN DEWANTARA, 2023)
This study aims to identify and analyze the effect of hedonic shopping motivation, shopping lifestyle, and sales promotion on impulse purchases at H&M Hartono Mall Yogyakarta outlets. This study used 100 respondents as a sample who were consumers who were making direct purchases at H&M Hartono Mall Yogyakarta. Sampling in this study using purposive sampling technique. This study uses multiple linear regression analysis. The results of this study prove that partially hedonic shopping motivation and sales promotion have a positive and significant effect on impulsive purchases at the H&M Outlet Hartono Mall Yogyakarta. Meanwhile, the shopping lifestyle has no significant effect on impulsive purchases at the H&M Hartono Mall Yogyakarta Outlet. Simultaneously hedonic shopping motivation, shopping lifestyle, and sales promotion have a positive and significant effect on impulsive buying at the H&M Hartono Mall Yogyakarta Outlet.